Crecimiento y mejora del índice gonadal en el cultivo del erizo de mar Paracentrotus lividus (Echinoida: Echinidae) en Galicia (España) - Rey-Mendez, Manuel; Touron, Noelia; Rodriguez-Castro, Belen; Rama-Villar, Antonio; Fernandez-Silva, Iria; González Henriquez, Nieves; Martinez, Dorotea; Ojea, Justa; Luis Catoira, Jose (2015)
The high demand for Paracentrotus lividus (Lamarck, 1816) in countries like France, Italy, Turkey, Belgium and Japan, has raised the level of extraction of this echinoderm in recent years and has generated wear urchin populations, which take years to regenerate. The economic importance of P. lividus in Galicia, with an average annual production of 700 <= 000 kg and a value close to (sic) 2 million in 2013, has led us to perform a variety of experiences in order to analyze the possibilities of the culture of this species in Galicia in raft. We have designed three experiences: 1) Effect of five diets and three densities on the growth of juvenile P. lividus obtained from the natural environment; 2) Growth of juvenile P. lividus obtained from hatchery, fed algae, and 3) Effect of different experimental diets on gonadal index of P. lividus commercial size. The experiments were performed on a USC raft situated in the estuary of Muros-Noia (Galicia) for four years (2007-2010), using 2 231 total urchins, from the natural environment (450), hatchery (773) and market size (1 008), being designed various experimental diets that try to increase somatic and gonadal growth in sea urchins, in order to reduce the rise time of juveniles from the wild and hatchery until they reach the size commercial (55 mm diameter), or until they get a suitable size to repopulate overfished areas of the natural environment (20 mm diameter), and the growth of the gonads of sea urchins with different diets. Monthly has taken diameter of juvenile sea urchins in order to determine the effect of different diets on growth and densities of the same, as well as determining the gonadal index (GI) in sea urchins of commercial size to see the effect took different tested diets. With the data obtained estimates that, at present, it would be profitable to feed juvenile sea urchins P. lividus in raft to reach commercial size, due to the low price of this species in the market (3(sic) / kg). Additonally they could reach optimum size and be used to ...